2010
DOI: 10.1136/sti.2009.038299
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the high prevalence of gonorrhoea and chlamydia among female sex workers in Indonesia: results of an enhanced, comprehensive intervention

Abstract: The STI-control programme was effective in reducing infection prevalence and increasing condom use among sex workers. This intervention has been scaled up and may decrease national STI levels and reduce HIV transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…HIV/STI prevalences among transactional and commercial sex workers in PNG were high in this review, and broadly comparable to those observed among similar populations in Indonesia[65], [66], [67], [68], the Philippines[69], [70] and other countries in SE Asia[71], [72], [73], [74], [75]. Prevalences among men and women in the general community however appear much higher in PNG (and in several other Pacific Island nations, such Fiji, Samoa and Vanuatu) than in SE Asia [76], [77].…”
Section: Discussionsupporting
confidence: 82%
“…HIV/STI prevalences among transactional and commercial sex workers in PNG were high in this review, and broadly comparable to those observed among similar populations in Indonesia[65], [66], [67], [68], the Philippines[69], [70] and other countries in SE Asia[71], [72], [73], [74], [75]. Prevalences among men and women in the general community however appear much higher in PNG (and in several other Pacific Island nations, such Fiji, Samoa and Vanuatu) than in SE Asia [76], [77].…”
Section: Discussionsupporting
confidence: 82%
“…As previous studies have indicated that these infections may result in increased risk of HIV transmission [8], it seems appropriate to focus on controlling STIs among waria in order to decrease HIV transmission. We have shown previously that periodic presumptive treatment for gonorrhea and chlamydia among female sex workers in Indonesia resulted in a rapid decline in prevalence of gonorrhea and Chlamydia [12]. A similar project has been developed by the Indonesian Ministry of Health for waria and the first round of presumptive treatment for gonorrhea and chlamydia has been provided for 250 waria in Surabaya in December 2009.…”
Section: Discussionmentioning
confidence: 96%
“…Brothel-based FSWs have experienced the highest increase, from 0.62% in 2000 to 20.16% in 2010 [8]. This high prevalence is accompanied by a high prevalence of gonococcal and chlamydial infections, both important factors in the high risk of HIV infection among brothel-based FSWs and clients [9]. Moreover, behavioural surveys in 2009, 2010 and 2011 show that consistent condom use among brothel-based FSWs remains below 40%, much lower than the national target to achieve a minimum 60% consistent condom use among high risk groups including FSWs [6].…”
Section: Introductionmentioning
confidence: 99%